Role of p38 and STAT5 Kinase Pathways in the Regulation of Survival of Motor Neuron Gene Expression for Development of Novel Spinal Muscular Atrophy Therapeutics - Farooq, Faraz T (Université d'Ottawa / University of Ottawa, 2012)
Spinal muscle atrophy (SMA) is an autosomal recessive neurodegenerative disease which is characterized by the loss of α motor neurons from the anterior horn of the spinal cord, resulting in progressive muscle atrophy. The loss of functional Survival motor neuron (SMN) protein due to mutations or deletion in the SMN1 gene is the cause of SMA. A potential treatment strategy for SMA is to upregulate levels of the SMN protein originating from the copy gene SMN2 which can compensate in part for the absence of the functional SMN1 gene. I have shown a novel therapeutic strategy for SMA treatment through the activation of the p38 pathway by the bacterial antibiotic anisomycin which stabilizes and increases SMN mRNA levels in vitro. Activation of the p38 pathway by anisomycin leads to cytoplasmic accumulation of HuR protein which binds to the 3’UTR of SMN transcript resulting in increased SMN levels. This opens up a novel potential therapeutic strategy for SMA. I have also identified and demonstrated a significant induction of SMN protein levels in vitro and in vivo upon treatment with FDA approved drug celecoxib, which also activates the p38 pathway. Celecoxib mitigates disease severity along with increasing the lifespan of SMA mice. Sodium valproate, trichostatin A and aclarubicin, all agents which effectively enhance SMN2 expression, have been recently shown to activate STAT5 in SMA-like mouse embryonic fibroblasts and human SMN2-transfected NSC34 cells. Given that prolactin is also known to activate the STAT5 signalling pathway, can cross blood brain barrier and is FDA approved, we elected to assess its impact on SMN levels. In this manner, I have demonstrated a significant induction in SMN mRNA and protein levels in neuronal NT2 and MN-1 cells upon treatment with prolactin. I have also demonstrated that activation of the STAT5 pathway by prolactin is necessary for this transcriptional upregulation of the SMN gene. I have found that prolactin treatment induces SMN expression in brain and spinal cord samples and that it ameliorates the disease phenotype, improving motor neuron function and increasing survival in the SMA mouse model. Presently there is no cure for SMA. This study will help in the identification and characterization of potential therapeutic compounds for the treatment of SMA.
Keywords: Anisomycin; Celecoxib; Novel therapeutics; p38 MAPK; Prolactin; SMA; SMN